2019
DOI: 10.1111/pbi.13226
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly of a wild pear (Pyrus betuleafolia) genome

Abstract: SummaryChina is the origin and evolutionary centre of Oriental pears. Pyrus betuleafolia is a wild species native to China and distributed in the northern region, and it is widely used as rootstock. Here, we report the de novo assembly of the genome of P. betuleafolia‐Shanxi Duli using an integrated strategy that combines PacBio sequencing, BioNano mapping and chromosome conformation capture (Hi‐C) sequencing. The genome assembly size was 532.7 Mb, with a contig N50 of 1.57 Mb. A total of 59 552 protein‐coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 66 publications
3
96
0
Order By: Relevance
“…With the development of sequencing technology, more and more species completed the whole-genome sequencing, such as P. betuleafolia (Dong et al, 2019), P. granatum (Yuan et al, 2018) and M. rubra (Jia et al, 2019). We generated the first highquality chromosomal level genome assembly of H. cannabinus var.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of sequencing technology, more and more species completed the whole-genome sequencing, such as P. betuleafolia (Dong et al, 2019), P. granatum (Yuan et al, 2018) and M. rubra (Jia et al, 2019). We generated the first highquality chromosomal level genome assembly of H. cannabinus var.…”
Section: Discussionmentioning
confidence: 99%
“…In cucurbita spp., the ratio was ~0.8 but only 9% of genetic variants showed HIGH or MODERATE impact in full genomic sequence, suggesting a great presence of intergenic mutations. In walnut tree genomic sequence, Marrano et al (2019) identified 2.8% potentially impacting variants, while in the pear genome 55% of mutations were classified as missense and 1% with HIGH impact (Dong et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The studies that produced these maps allow the possibility of constructing complete molecular karyotypes for these species. Whole-genome sequences of apple [93,94], pear [95,96], strawberry [97], peach [98], Prunus mume [99], sweet orange [100], jujube [101], pineapple [102], and kiwifruit [103], as well as those of rice, maize, wheat, soybean [104], have been published; therefore, we can obtain large numbers of conserved SSR markers located in the centromeres and telomeres from these whole-genome sequences. Therefore, molecular karyotyping using SSR markers and qPCR is a very useful tool for basic genetic research and accurate breeding.…”
Section: Ssr-qpcr Allows the Application Of Molecular Karyotyping Tomentioning
confidence: 99%